Regla de Oro, sostenibilidad y regla fiscal contracíclica - Jimenez, Félix (2005)
The current fiscal policy does not differentiate capital expenditure from current expenditure. Since the global deficit target is fixed according to the present fiscal policy rule, the non financial expenditure becomes pro cyclical, and the public investment is adjusted to meet the targeted deficit. As a result, the public investment has dramatically decreased which, in turn, has affected the international competitiveness and the economic and social development of the Peruvian society. This paper proposes: 1) change the public expenditure policy public investment by eliminating its pro cyclical bias; and 2) redefining the system of fiscal accounting. To meet this purposes the budget must be divided in two parts: the current budget with a saving or primary surplus target, and the investment expenditure based on a rule of directing the public debt only to finance this kind of expenditure over the economic cycle. This is the so called Public Investment Golden Rule. To this Golden Rule is added other according to which the ratio of public net debt must be sustainable during the economic cycle. Finally, it’s proposed to adopting the new IMF accounting system. The Golden Rule becomes pretty velar in the context of this new system. When the operational result becomes equal to cero, the net investment becomes equal to the public debt. Hence, the null operational result according to the new accounting system is the only one which is consistent with the Golden Rule.